Review of: Time in Child Inuktitut: A Developmental Study of an Eskimo-Aleut Language - Vajda, Edward J. (Western CEDAR, 2007)
Most studies of child language acquisition up till now have focused on Indo-European or the major languages of East Asia. An investigation of how children master the typologically very different structure of a language such as Inuktitut is therefore of considerable theoretical interest. This book describes how children up to the age of three and a half acquire the mechanisms of time reference in the Tarramiut (Hudson Strait) subdialect of Inuktitut, a language spoken by about fifteen hundred Inuit in arctic Quebec.